2021
DOI: 10.3126/jncs.v42i1.35332
|View full text |Cite
|
Sign up to set email alerts
|

Oxovanadium(IV) Complexes with Triazole Based Schiff Base Ligands: Synthesis, Characterization and Antibacterial Study

Abstract: Schiff bases have been synthesized by the reaction of triazole containing primary amine with aromatic carbonyl compounds. The Schiff bases prepared, act as ligand when these are made in contact with oxovanadium (VO2+) ion. Some new mononuclear oxovanadium(IV) complexes have been synthesized by the reaction of Schiff base ligands with vanadyl sulphate (VOSO4.xH2O)  and the complexes are analyzed by different spectroscopic methods; [fourier-transform infrared (FTIR), ultraviolet-visible (UV-Vis.), electron param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The cyclic voltammograms for the complexes display the peak-to-peak separation, ΔE p to be ~59 mV and 30 mV for a one-electron and two-electron processes respectively in an ideal reversible scenario [6,12]. But in this study for both ML 1 and ML 2 complexes, the peak-to-peak separation is slightly larger, and the peak current ratio is nearly the same as in the oneelectron ideal reversible process.…”
Section: Conductance and Cyclic Voltammetry (Cv) Analysismentioning
confidence: 50%
“…The cyclic voltammograms for the complexes display the peak-to-peak separation, ΔE p to be ~59 mV and 30 mV for a one-electron and two-electron processes respectively in an ideal reversible scenario [6,12]. But in this study for both ML 1 and ML 2 complexes, the peak-to-peak separation is slightly larger, and the peak current ratio is nearly the same as in the oneelectron ideal reversible process.…”
Section: Conductance and Cyclic Voltammetry (Cv) Analysismentioning
confidence: 50%
“…In addition, the absorption peak near 1453 cm −1 was assigned to the −C=C− of the benzene ring skeleton in the ligand. The results only showed that the Schiff base ligands formed, but the difference of the two different Schiff base ligands was characterized difficultly by FTIR [7] …”
Section: Resultsmentioning
confidence: 98%
“…The results only showed that the Schiff base ligands formed, but the difference of the two different Schiff base ligands was characterized difficultly by FTIR. [7] To further confirm the chemical structure of the ligand obtained in the reaction process and the ligand precipitated from the reaction solution after adding ether, the ligands were characterized by 1 H NMR, 13 C NMR and MS and the results were shown in Figure 2, Figure 3 and Figure 4. 1 H NMR and 13 C NMR spectra of the ligand obtained in the reaction process was consistent with that of the ligand precipitated from the reaction mixture after adding ether and the results were showed in Figure 2 and Figure 3.…”
Section: Chemistryselectmentioning
confidence: 99%
“…A more stable complex is one that is less likely to dissociate into its component ions, which is indicated by a larger value of (β j ). The complex's behavior under various conditions can be predicted using the stability constants, and experiments can be created to better understand the complex's properties [ [48] , [49] , [50] , [51] , [52] ]. The following Equations 29–31 are used to compute the stability constants (β j ) of the copper complex for each addition : where E° M is the formal peak potential of copper ions at final addition in the absence of indomethacin, E° C is the formal peak potential of the copper complex after each addition of indomethacin, the coordination number of the stoichiometric complex is j, the concentration of indomethacin in the solution is C x , the formal potential is E°, the anodic peak potential is Ep a , the cathodic peak potential is Ep c , the stability constant is β j , and the Gibbs free energy of the interaction between copper ions and indomethacin is ΔG.…”
Section: Resultsmentioning
confidence: 99%